People's participation and convergence of Institutions in watershed development in eastern ghats of India: An experience - Sudhishri, Susama; Dass, Anchal; Choudhury, P.R.; Kumar, Pramod; Lenka, N.K.; Patnaik, U.S. (Annals of Agricultural Research, 2016)
Participatory integrated watershed management is considered to be an ideal way of sustainable development. It emphasizes on the participation and contribution of the stakeholders in terms of cash and kind. For wide spreading of the technologies and use of financial capital in a very extensive way convergence of line departments plays an important role. The present paper is based on the outcome and experiences gained, while applying such theses for the sustainable holistic development of a tribal watershed, Kokriguda, in Koraput district of Odisha falling in the eastern ghats region of India. A number of interventions were undertaken based on the problems, perceptions, needs and priorities of the villagers as per PRA exercises. Persistent efforts and enduring patience of them watershed development team could win their faith. Different entry point activities (EPAs) proved fruitful in providing further impetus to the participation process by converging different institutions in the vicinity. Obviously, gaining confidence and motivation of the community were the natural offshoots of the EPA. Strengthening of local institutions viz. Watershed Association (WA), Watershed Committee (WC), Self Help Groups (SHGs), User Groups (UGs), Water User's Association (WUA), etc. and converging all line departments were the associated complementary measures. The villagers extended their contribution in the form of labour ranging from 5-100% in different interventions.